Seasonal variability of mercury contents in street dust in Brno, Czech Republic - Coufalík, Pavel; Zvěřina, Ondřej; Mikuška, Pavel; Komárek, Josef (Bulletin of environmental contamination and toxicology, 2014)
Environmental contamination by mercury carries serious risks to the biosphere. Urban agglomerations burdened with traffic are characterized by substantial dust levels, including high concentrations of pollutants bound to particulate matter. In this research, the content of particulate mercury in street dust was investigated in relation to the season and traffic intensity. In total, 80 street dust samples were collected in the centre of Brno (Czech Republic) in which total and bioaccessible mercury contents were determined. Total mercury content in the samples ranged from 0.03 to 2.67 mg/kg. The content of bioaccessible mercury was below the limit of quantification in all samples. Thus, street dust did not increase the daily mercury intake by the population in studied area. A clear trend of mercury accumulation in street dust depending on traffic intensity in the investigated streets was not observed over the whole year.
Keywords: spektrofotometrie atomová; Spectrophotometry, Atomic; Česká republika; Hazardous Substances; rtuť; Mercury; znečištění životního prostředí; Environmental Pollution; nebezpečné látky; Seasons; prach; Czech Republic; Dust; roční období; Environmental Monitoring; monitorování životního prostředí